2022
DOI: 10.7717/peerj.14147
|View full text |Cite
|
Sign up to set email alerts
|

A novel alkane monooxygenase (alkB) clade revealed by massive genomic survey and its dissemination association with IS elements

Abstract: Background Alkanes are important components of fossil energy, such as crude oil. The alkane monooxygenase encoded by alkB gene performs the initial step of alkane degradation under aerobic conditions. The alkB gene is well studied due to its ubiquity as well as the availability of experimentally functional evidence. The alkBFGHJKL and alkST clusters are special kind of alkB-type alkane hydroxylase system, which encode all proteins necessary for converting alkanes into corresponding fatty acids. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Pseudomonas sp. strain RW407 was isolated from polluted sediment of the Elbe River in Germany, Pseudomonas citronellolis strain P3B5 was isolated from the basil plant phyllosphere, and strain 273 was obtained from garden soil collected in the Stuttgart area, Germany. , The high sequence similarity between alkB -2 of strain 273 and the alkB genes of strain RW407 and strain P3B5 could indicate horizontal gene transfer, an observation supported by a recent study that analyzed alkB genes in a genomic context and concluded that horizontal gene transfer events contribute substantially to the dissemination of alkB genes …”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Pseudomonas sp. strain RW407 was isolated from polluted sediment of the Elbe River in Germany, Pseudomonas citronellolis strain P3B5 was isolated from the basil plant phyllosphere, and strain 273 was obtained from garden soil collected in the Stuttgart area, Germany. , The high sequence similarity between alkB -2 of strain 273 and the alkB genes of strain RW407 and strain P3B5 could indicate horizontal gene transfer, an observation supported by a recent study that analyzed alkB genes in a genomic context and concluded that horizontal gene transfer events contribute substantially to the dissemination of alkB genes …”
Section: Discussionmentioning
confidence: 72%
“…18,59 The high sequence similarity between alkB-2 of strain 273 and the alkB genes of strain RW407 and strain P3B5 could indicate horizontal gene transfer, an observation supported by a recent study that analyzed alkB genes in a genomic context and concluded that horizontal gene transfer events contribute substantially to the dissemination of alkB genes. 61 The comparative transcriptome analysis revealed a unique AlkB alkane monooxygenase with a novel AlkB Fd-Rd architecture involved in the initial attack on decane and DFD. AlkB-2 is the first enzyme of this type implicated in oxygenolytic defluorination, offering opportunities to investigate features distinguishing AlkB enzymes that attack a terminal fluoromethyl group.…”
Section: And Biogenesis [J] Transcription [K] Signal Transduction Mec...mentioning
confidence: 99%
“…Sofar, M. nauticus has been reported to have the capacity for pollution degradation. For instance, M. nauticus has been described to degrade an acyclic saturated hydrocarbon (alkane) under aerobic conditions due to its capacity to synthesize alkane monooxygenase (Wang et al, 2022). Another study reported that M. nauticus isolated from water of an oil field in Vietnam was able to grow in wide ranges of temperatures (13°C–50°C) and salinity (0–20% NaCl) (Huu et al, 1999), therefore consider as a halotolerant bacterium (Tourova et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Los clusters de genes alkB codifican todas las proteínas necesarias para convertir los alcanos en los correspondientes ácidos grasos, dotando a los microorganismos con la habilidad de utilizar alcanos como única fuente de carbono y energía (Wang et al 2022). Usualmente, existe un gen por genoma, aunque en algunas especies se han hallado dos o más genes alkB redundantes (Whyte et al 2002).…”
Section: Introductionunclassified